VARIASI FORMULA PUMAKKAL TERHADAP KADAR N, P, K PUPUK CAIR LIMBAH PASAR IKAN SEBAGAI BAHAN AJAR BIOLOGI LEMBAR KERJA PESERTA DIDIK (LKPD) - Anggit Khendio Utomo; Agus Sutanto; Widya Sartika Sulistiani; Hening Widowati; Rasuane Noor (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
Fisheries are one of the trade commodities that are favored by the public for consumption, both freshwater fish and seawater fish. Fish is much favored by the community in addition to having a good taste as well as an affordable price. From the high interest in fish consumption, traditional markets cause pollution to the environment. The pollution is in the form of waste fish. This research was conducted as a solution to overcome the problem of fish market liquid waste that can be used as raw material for making liquid organic fertilizer by optimizing the utilization of the Pumakkal starter. In this study, treatment was carried out with 1 control and 5 treatments, and 3 replications. P1 with a varied formula of 3 isolates, P2 with a variety of formula 6 isolates, P3 with a variety of formula 9 isolates, P4 with a variation of formula 12 isolates, and P5 with a variation of formula 15 isolates. The research results show that levels of N + P + K has a quality standard set by the government (2-6%). In the P0 treatment, the percentage of N+P+K was 5.685%. Then in the P1 treatment, the percentage of N+P+K was 6.998%. Then in the P2 treatment, the percentage of N+P+K was 7.727%. Then in the P3 treatment, the percentage of N+P+K was 8.430%. Furthermore, in the P4 treatment, the percentage of N+P+K was 8.284%. Meanwhile, for the P5 treatment, the percentage of N+P+K was 9.658%. At levels of C-Organic, it has a quality standard (minimum 10) with a percentage of 18.208%. For the value of C-Organic with a percentage of already complied with the provisions of SNI. For the levels of N+P2O5+K2O with a percentage of 12,239%. The measured pH level, it has a value of 6. Then the liquid organic fertilizer from fish market waste is said to be feasible because it meets the criteria of SNI or Regulation of the Minister of Agriculture no. 261/KTPS/SR. 310/M4/2019.